Small area synthetic estimates of smoking prevalence during pregnancy in England - Szatkowski, Lisa; Fahy, Samantha; Coleman, Tim; Taylor, Joanna; Twigg, Liz; Moon, Graham; Leonardi-Bee, Jo (BioMed Central, 2015)
Background Complete and accurate data on maternal smoking prevalence during pregnancy are not available at a local geographical scale in England. We employ a synthetic estimation approach to predict the expected prevalence of smoking during pregnancy and smoking at delivery by Primary Care Trust (PCT).